2020
DOI: 10.3390/cancers12102842
|View full text |Cite
|
Sign up to set email alerts
|

(2R,3S)-Dihydroxybutanoic Acid Synthesis as a Novel Metabolic Function of Mutant Isocitrate Dehydrogenase 1 and 2 in Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) frequently harbors mutations in isocitrate 1 (IDH1) and 2 (IDH2) genes, leading to the formation of the oncometabolite (2R)-hydroxyglutaric acid (2R-HG) with epigenetic consequences for AML proliferation and differentiation. To investigate if broad metabolic aberrations may result from IDH1 and IDH2 mutations in AML, plasma metabolomics was conducted by gas chromatography–mass spectrometry (GC–MS) on 51 AML patients, 29 IDH1/2 wild-type (WT), 9 with IDH1R132, 12 with IDH2R140 and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…2) as described. [25][26][27][28] A principal components analysis (PCA) scores plot showing clustering of the QC sample scores is shown in Supplementary Fig. S1.…”
Section: Mouse Body Weightmentioning
confidence: 99%
“…2) as described. [25][26][27][28] A principal components analysis (PCA) scores plot showing clustering of the QC sample scores is shown in Supplementary Fig. S1.…”
Section: Mouse Body Weightmentioning
confidence: 99%
“…Firstly, the hotspots for serum creatinine concentration (crtn) with 2,3-dihydroxybutanoic acid (2,3-D) in both postoperative drainage fluid and ascites fluid may be related to their respective renal handling. This latter compound is the (2R,3S)-dihydroxybutanoic acid diastereomer, a metabolite of threonine and a putative oncometabolite in acute myeloid leukemia [13,46]. Its water solubility has been estimated as 454 g/L using artificial neural networks [47], considerably greater than creatinine water solubility (90 g/L).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that 2,3-DHBA is synthesized by mutant IDH1 and IDH2 similarly to the synthesis of 2R-HG from 2-OG. Moreover, we have also suggested that the precursor of 2,3-DHBA in this reaction is (3S)-hydroxy-2-oxobutanoate formed by the transamination of the amino acid L-threonine (Figure 3) [33]. The properties of 2,3-DHBA with respect to cancer cell proliferation and its epigenetic regulation are yet to be established.…”
Section: Miscellaneousmentioning
confidence: 90%
“…The current NIST/EPA/NIH EI-MS library contains over 350,000 spectra. We adopted a GC-MS metabolomic workflow to interrogate the small intermediary metabolite component of the plasma [29][30][31][32][33], urine [30], liver [31,34] and cultured cell [35,36] metabolomes. Others have utilized gas chromatography coupled to a time-of-flight mass spectrometer (GC-TOFMS) in cancer research [37].…”
Section: Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation